2016
DOI: 10.1016/j.arth.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Damage and Wear Mechanisms in Long-Term Retrieved CoCr Femoral Components for Total Knee Arthroplasty

Abstract: Background Metal debris and ion release has raised concerns in joint arthroplasty. The purpose of this study was to characterize the sources of metallic ions and particulate debris released from long-term (in vivo > 15y) TKA femoral components. Methods A total of 52 CoCr femoral condyles were identified as having been implanted for more than 15 years. The femoral components were examined for incidence of five types of damage (metal-on-metal wear due to historical polyethylene insert failure, MACC at taper in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 15 publications
3
49
2
Order By: Relevance
“…Retrieval analyses have received more attention in the last years as these studies have provided an exclusive insight into how wear affects the hard femoral component besides the more softer insert made of different types of polyethylene [2, 14, 17, 24]. Currently, no data exist to explain the sensitivity of TiN-coated TKAs made of CoCrMo with regard to surface damage and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Retrieval analyses have received more attention in the last years as these studies have provided an exclusive insight into how wear affects the hard femoral component besides the more softer insert made of different types of polyethylene [2, 14, 17, 24]. Currently, no data exist to explain the sensitivity of TiN-coated TKAs made of CoCrMo with regard to surface damage and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Their excellent corrosion resistance relies on the formation of very stable, continuous, highly adherent and protective passive film on the metallic surface (Milosev, 2012). This passive film prevents degradation of the alloys as is one of the kinetic barriers preventing implant corrosion (Arnholt et al, 2016). However, due to wear, electrochemical dissolution, or a combination of the 2 processes, micro and nanometric sizes wear particles are still produced and metallic ions are released from the prosthesis of the implanted patients (Billi et al, 2009;Hosman et al, 2010;Arnholt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This passive film prevents degradation of the alloys as is one of the kinetic barriers preventing implant corrosion (Arnholt et al, 2016). However, due to wear, electrochemical dissolution, or a combination of the 2 processes, micro and nanometric sizes wear particles are still produced and metallic ions are released from the prosthesis of the implanted patients (Billi et al, 2009;Hosman et al, 2010;Arnholt et al, 2016). Catelas et al (2003) have reported the necessity to carry out in vitro studies of the effects of these wear particles rather than the effect of CoCrMo particles on tissue response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of metal loss are multifactorial and can include mechanically assisted crevice corrosion (MACC), wear at the bearing surfaces and the recently described phenomenon of inflammatory cell‐induced corrosion (ICIC) . ‐ …”
Section: Introductionmentioning
confidence: 99%